The Legitimacy of Unmanned Aerial Vehicle Usage in International Humanitarian Law - L.Ya Esty Pratiwi (Faculty of Law, Muhammadiyah University of Surabaya, 2023)
The use of drones as a weapon in the battlefield has raised various issues, especially concerning the protection of civilian populations and compliance with the principles of IHL (International Humanitarian Law). Although there are no specific international regulations governing the use of drones, flexible principles of IHL can be applied. However, the use of drones for armed attacks has raised questions about the legality and state responsibility for their impact. In the context of the United States, the use of drones has raised concerns regarding violations of IHL and international law. Protecting civilians under IHL and distinguishing between military and non-military targets are primary concerns in assessing the use of drones as weapons. Furthermore, the need for stricter international regulations and state accountability in the use of drones is also highlighted in this article. Thus, this article presents an in-depth analysis of the legal challenges and implications of drone use in wartime situations, as well as emphasizing the need for a clear regulatory framework within the context of international law. Keywords: Keywords: Civilian population, Legality and accountability of states, International law